The New Maximum Length and Depth of Lagocephalus guentheri Miranda Ribeiro, 1915 in the Mediterranean Sea - Nur Bikem Kesici; Cem Dalyan; Onur Gönülal (Turkish Journal of Bioscience and Collections)
In this study, one specimen of Lagocephalus guentheri, the largest individual (536 mm) ever recorded, was obtained from the Iskenderun Bay, Levantine Sea. The specimen was caught from two nautical miles off the Samandağ coast at a depth of 128 m with a commercial trawler. The present finding reports the maximum length and the deepest record of the species for the Mediterranean Sea. Apparently, the distribution of the species in the Mediterranean Sea will expand in the following years.